Pengaruh Konsentrasi Ekstrak Daun Eboni dan Daun Sirsak Terhadap Retensi Bahan Pengawet pada Kayu Durian (Durio zibethinus): The Effect of Concentration of Ebony and Soursop Leaves Extracts on Retention of Preservatives in Durian Wood - Asniati; Muthmainnah (KOVALEN: Jurnal Riset Kimia, 2022)
Durian wood is one type of wood that has a low level of durability, therefore it is necessary to make efforts to increase the durability of wood. These efforts can be done by preserving the durian wood by using natural preservatives, namely ebony leaves extract and soursop leaves. Ebony and soursop leaves extracts were used as natural preservatives with different concentrations using the cold soak method on durian wood. The research conducted aims to determine the effect of extract concentration on the retention of preservatives. Ebony leaves and soursop leaves were extracted by maceration method in 96% ethanol solvent for 24 hours. The durian wood sample was preserved using the cold soaking method for 1 hour using ebony leaves extract and soursop leaves extract at concentrations of 1%, 2%, and 3%. The results showed that the highest retention of preservatives from ebony leaves extract and soursop leaves extract was the use of 3% concentrations of 0.661 kg/m³ and 0.676 kg/m³, respectively. The results of the analysis of variance showed that the extract concentration had a significant effect on the retention value. The concentration of preservatives from ebony leaves extract and soursop leaves is directly proportional to the retention value of preservatives. Preservative retention of soursop leaves extract is better than ebony leaves extract.